On the Sensitivity of Boolean and Multiple-Valued Symmetric Functions - Butler, Jon T.; Sasao, Tsutomu (Proceedings / International Symposium on Multiple-Valued Logic, 2022)
An n variable Boolean logic function f(\vec{x}) is sensitive to x_{i} if there is at least one assignment of values to \vec{x}-\{x_{i}\} such that f changes when x_{i} changes. We investigate the sensitivity of Boolean logic functions experimentally. For example, we show the use of a reconfigurable computer in computing the sensitivity of n -variable Boolean functions with up through n=5 variables. For n=5 , this computation is 192 times faster than a single Xeon microprocessor and 1.8 times faster than a cluster computer with 256 processors. We also examine sensitivity in multiple-valued logic functions.